The Influence of Longitudinal Stiffeners on Weld Toe Stress Concentrations in Multi Planar Tubular KK joints - Woghiren, Charles O.; Brennan, Feargal P. (Trans Tech Publications, 2007)
This paper reports a parametric stress analysis of various configurations of rack plate stiffened multi-planar welded KK joints using the finite element method. The KK joint finds application in the leg structure of offshore Oil & Gas jack-up platforms. The rack plate is a dual purpose element of the joint because it firstly functions as a stiffener which reduces the stress concentration at the brace/chord intersection. This could be an immense contribution to the increase in fatigue life of the joint but other hot spot sites are introduced to the joint. The rack is also used for raising and lowering of the jack-up hull which gives the jack-up platform its jacking capability. Over 120 models using a combination of shell and solid elements were built and analysed within ABAQUS. Non-dimensional joint geometric parameters; β, γ and Ω were employed in the study with Ω being defined as the ratio of rack thickness to chord diameter. Stress Concentration Factors (SCFs) were calculated under applied axial and OPB (out-of-plane-bending) loading. Three critical SCF locations were identified for each load case, with each location becoming the most critical based on the combination of the non-dimensional parameters selected for the joint. This is important as careful design can shift the critical SCF from an area inaccessible to NDT to one that can be easily inspected. The SCF values extracted from the models were used to derive six parametric equations through multiple regression analysis performed using MINITAB. The equations describe the SCF at the different locations as a function of the non-dimensional ratios. The equations not only allow the rapid optimisation of multi-planar joints but also can be used to quickly identify the location of maximum stress concentration and hence the likely position of fatigue cracks. This in itself is an invaluable tool for planning NDT procedures and schedules.
Keywords: Tubular Joints; Stiffened Tubular Joints; Multi Planar Tubular Joints; Welded Tubular Joints; Stress Concentration; Parametric Equations